The way of Reducing the Losses of Agricultural Products in Harvesting - Djuraev Bekzod; Kamolov Asliddin (International Journal on Orange Technologies, 2021)
All types of natural products that which grown on agricultural are considered to be beneficial for human health. At the same time, regardless of how important it is for the human organism, agricultural products grown for the production of all kinds of fruits, vegetables, spices and processed consumer goods are food. We are known that there are also two types of agricultural food products, such as agriculture and livestock, but the importance of fruits and vegetables for human health is higher. According to nutritionists that fruits and vegetables are plenty in all the minerals necessary for human health and play an important role in boosting immunity. Accordingly, it is recommended that a healthy person consume an average of 80-100 grams of fruits and 360 grams of vegetables per day.